Age and growth of bamboo coral Isidella elongata (Esper, 1788): a Mediterranean Vulnerable Marine Ecosystem indicator taxa - Pierluigi Carbonara; Giovanni Chimienti; Andrea Bellodi; Rigers Bakiu; Isabella Bitetto; Lucio Calcagnile; Marisa D’Elia; Maria C. Follesa; Aurora Nastasi; Michele Palmisano; Walter Zupa; Gianluca Quarta (Coral Reefs, 2025)

Anticipating how spatial fishing restrictions in EU waters perform to protect marine species, habitats, and dependent fisheries - François Bastardie; Amaia Astarloa; Logan Binch; Isabella Bitetto; Dimitrios Damalas; Jochen Depestele; Pierre-Yves Hernvann; Sigrid Lehuta; Jonas Letschert; Irida Maina; Stéphanie Mahévas; Georgia Papantoniou; et al. (Frontiers in Marine Science, 2025)
This study investigates the implications of spatial management strategies on fish populations and fisheries across EU waters, particularly focusing on establishing potential areas for fishing closures to protect nurseries, benthic communities, and biodiversity hotspots in the Northeast Atlantic and Mediterranean Sea. The research addresses the effectiveness of prohibiting certain fishing practices in the context of the EU Common Fisheries Policy (CFP). We investigate spatial- and effort-based fisheries management strategies based on spatial ecosystem modelling, which provides insights into species interactions and distribution shifts, and bioeconomic fisheries models which incorporate finely defined fishing fleets and economic dynamics. Our findings emphasize that redistributing fishing effort without reducing overall effort and catches may negate intended decreases in mortality rates of sensitive marine species or restoration of vulnerable marine habitats to the status targeted by the European marine legislation (EU Marine Strategy Framework Directive MSFD). We highlight the complex interplay of social, economic, ecological, and institutional factors influencing fishers’ decision-making in effort displacement. As the proportion of closed regions increases, potential effects on marine ecosystems can even be damaging in the short term to some sensitive species (such as the endangered, threatened and protected species ETP) and vulnerable habitats (with currently high relative benthic status RBS). This emphasizes the importance of the placement of closed areas and of combining area-based management with other fishery management measures. Findings from case studies in the North Sea, Mediterranean Sea, and Bay of Biscay indicate that prohibiting certain fishing practices in designated areas will likely induce short-term economic losses on specific fishing fleets. Where the prohibitions contribute to improved selectivity or productivity of the fish stocks, these losses may be regained in the long term. Finally, the long-term benefits for marine life that are expected through the spatial protection of vulnerable life stages and habitats will rely on the extent to which climate change affects ocean productivity and distribution of species and habitats.

Improved volcanic SO2 flux records from integrated scanning-DOAS and UV Camera observations. - Giovanni Lo Bue Trisciuzzi; Alessandro Aiuppa; Giuseppe Salerno; Marcello Bitetto; Luciano Curcio; Lorenzo Innocenti; Giorgio Lacanna; Joao Pedro Nogueira Lages; Francesco Maria Lo Forte; Salvatore Roberto Maugeri; Filippo Murè; Paolo Principato; et al. (Journal of Volcanology and Geothermal Research, 2024)

Age validation of the European Anchovy (Engraulis encrasicolus Linnaeus, 1758) in the Central-Southern Tyrrhenian Sea (West Mediterranean Sea) - Pierluigi Carbonara; Andrea Bellodi; Andrea Massaro; Gualtiero Basilone; Loredana Casciaro; Michele Palmisano; Isabella Bitetto; Maria Cristina Follesa (Regional Studies in Marine Science, 2023)

Space utilization by key species of the pelagic fish community in an upwelling ecosystem of the Mediterranean Sea - A. Bonanno; M. Barra; R. Mifsud; G. Basilone; S. Genovese; M. Di Bitetto; S. Aronica; G. Giacalone; I. Fontana; S. Mangano; R. Ferreri; M. Pulizzi; et al. (Hydrobiologia, 2018)

Preference Modeling to Support Stakeholder Outreach toward the Common Fishery Policy Objectives in the North Mediterranean Sea - Giuseppe Lembo; Jose M. Bellido; Isabella Bitetto; Maria T. Facchini; Teresa García-Jiménez; Mavra Stithou; Vassiliki C. Vassilopoulou; Maria T. Spedicato (Frontiers in Marine Science, 2017)

A Holistic Approach to Fishery Management: Evidence and Insights from a Central Mediterranean Case Study (Western Ionian Sea) - Tommaso Russo; Isabella Bitetto; Pierluigi Carbonara; Roberto Carlucci; Lorenzo D'Andrea; Maria T. Facchini; Giuseppe Lembo; Porzia Maiorano; Letizia Sion; Maria T. Spedicato; Angelo Tursi; Stefano Cataudella (Frontiers in Marine Science, 2017)

Characterization of mitochondrial dicarboxylate/tricarboxylate transporters from grape berries - Ana Regalado; Ciro Leonardo Pierri; Maria Bitetto; Valentina Liliana Laera; Catarina Pimentel; Rita Francisco; José Passarinho; Maria M. Chaves; Gennaro Agrimi (Planta, 2013)